AKAD KAFALAH DALAM PERSPEKTIF FILSAFAT DITINJAU DARI ASAS KEMASLAHATAN - Abdul Hanif (IAIN Ambon, 2019)
This writing use the analysis description method try to describe the kafalah implementation in a Philosophy perspective reviewed from the principle of benefit implied in it. By pointing it out the principle of benefit which is studied wisely through the study of his philosophy. The results of study analysis in the Philosophy Perspective in the implementation of kafalah which is reviewed from the principle of benefit, they are: 1) Maslahah Mursalah 2) Maslahah Mu’tabarah dan 3) Maslahah Mulghah. In reviewing kafalah in the frame of peace at least the problem must be correlated with maqashid al-syariah al-khamsah: 1) hifz al-din, 2) hifz al-nafs, 3) hifz al-nasl, 4) hifz al-‘aql, dan 5) hifz al-mal. A benefit will be achieved if maqashid al-syariah al-kaffah become the main guideline in taking advantage.